بطالة خريجي الجامعة (أسبابها و آثارها)، دراسة سوسيولوجية ميدانية لعينة من خريجي الجامعة العاطلين عن العمل في مدينة السليمانية - محمد, ا.م.د.كەژاڵ حسين; عبدالله, م.م سورێن ابوبكر (Sulaimani Journal for Humanities, 2021)
Student university jobless (factors and affects) the research which present jobless university of Sulimaniay students graduation. The research shows the sample who were university graduation student at university of Sulimaniy, who are jobless. The research present the most important factors which reason to jobless phenomena among young people, also it shows the economic and social consequence of graduation student jobless. This research is description research based of using social survey, with using questioner to collect data information, which disturbed 75 forms among samples which taken by the snowball sampling form. Following some result of research: Graduation jobless has directly social and economic consequence on young people. Present some reasons why we can take benefited from graduation student knowledge and occupation in properly way. There is no strong link and adaption between university skills department for student with job opportunities in shop.
Keywords: Key concept Jobless; Unemployment; Graduation jobless; University